JANUBIY IQTISODIY RAYON QISHLOQ TUMANLARI NOMLARINING GEOGRAFIK XUSUSIYATLARI - Bayqabilov, X.M.; Sharipov, K.F. (SCIENCE and SOCIETY, 2024)
This article describes the geographical features of the names of rural districts of the Southern Economic Region in our country. The article also talks about the lexical-stratigraphic layers of district names and controversial issues related to naming.
Keywords: economic region; toponymic politics; geographical features of names; lexical-stratigraphic layers